Assessment of a decontamination process for dioxins and PCBs from fish meal by replacement of fish oil. (12th February 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on the assessment of a decontamination process of fish meal. It consisted of extraction of the fish oil, filtration and adsorption with activated carbon, and replacement with decontaminated fish oil in order to reduce the amount of dioxins (polychlorinated dibenzo‐ p ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs)), and dioxin‐like (DL‐) and non‐dioxin‐like (NDL‐) polychlorinated biphenyls (PCBs). All feed decontamination processes must comply with the acceptability criteria specified in the Commission Regulation (EU) 2015/786. Data provided by the feed business operator were assessed for efficacy of the process and to demonstrate that the process did not adversely affect the characteristics and the nature of the product. The process was effective in removing PCDD/Fs (97%) and DL‐ and NDL‐PCBs (93%). The fish meal produced complied with EU regulations for these contaminants. The Panel considered that the reference to information available in published literature was a pragmatic approach to demonstrate that the replacement of fish oil and the use of activated carbon to adsorb these contaminants does not lead to any detrimental changes in the nature of the fish meal. However, it was noted that the process could deplete some beneficial constituents (e.g. oil‐soluble vitamins). Information was provided to demonstrate the safe disposal of the waste material. The CONTAM Panel concluded that on the basis of the information submitted by the feed business operator the proposed decontamination process to remove dioxins (PCDD/Fs) and PCBs from the fish meal by oil extraction followed by replacement with decontaminated fish oil, was compliant with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015.